PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT KONSUMEN DI PEGADAIAN KOTA BATAM (Studi Kasus Pada Pegadaian Tiban Kampung, Batam Tahun 2012) - Pradana, Ferian Anugrah; Ukhriyawati, Catur Fatchu; Hasibuan, Rahman (BENING, 2015)
This research aims  to  determine  the  influence  of  Promotion  and Service  Quality  on  Consumer  interest  in  the  office  of  the  district  of Tiban  Kampung  Batam  City,  as well as  proving  there  is  or whether  the  relationship  between  these  variabel  as  seen from  the phenomena  that  occur  in  the  presence  of  the  costumer   in  the  office  the  District  of  Tiban  Kampung  Batam  City.The  data  are  collected  with  a  questionnaire  on  87  costumer.  Research  on  data  analysis  using  SPSS  version   20.  Data  collection   technique   in  the  quantitative   research used  is  a  descriptive  analysis  and  analysis  of  inferensial.The  research  resulted  in  that  there  was  a  relationship  very  closely  between  promotion  (X1)  on  the  consumer  interest   (Y),  There  is  a  positive  and  significant    effect  service quality  (X2)  on  the  performance  of  consumer  interest  (Y).  There  is  a  positive  and  significant  effect  simultaneously between  promotion  (X1)  and  service  quality  (X2)  on  the  consumer  interest  (Y) the equation of  Yi  = 0,385  –  X1  (0,007) + X2 (0,796).